MassBank: a public repository for sharing mass spectral data for life sciences - Horai, Hisayuki; Arita, Masanori; Kanaya, Shigehiko; Nihei, Yoshito; Ikeda, Tasuku; Suwa, Kazuhiro; Ojima, Yuya; Tanaka, Kenichi; Tanaka, Satoshi; Aoshima, Ken; Oda, Yoshiya; Kakazu, Yuji; et al. (Journal of mass spectrometry., 2010)
MassBank is the first public repository of mass spectra of small chemical compounds for life sciences (<3000 Da). The database contains 605 electron-ionization mass spectrometry(EI-MS), 137 fast atom bombardment MS and 9276 electrospray ionization (ESI)-MSn data of 2337 authentic compounds of metabolites, 11 545 EI-MS and 834 other-MS data of 10 286 volatile natural and synthetic compounds, and 3045 ESI-MS² data of 679 synthetic drugs contributed by 16 research groups (January 2010). ESI-MS² data were analyzed under nonstandardized, independent experimental conditions. MassBank is a distributed database. Each research group provides data from its own MassBank data servers distributed on the Internet. MassBank users can access either all of the MassBank data or a subset of the data by specifying one or more experimental conditions. In a spectral search to retrieve mass spectra similar to a query mass spectrum, the similarity score is calculated by a weighted cosine correlation in which weighting exponents on peak intensity and the mass-to-charge ratio are optimized to the ESI-MS² data. MassBank also provides a merged spectrum for each compound prepared by merging the analyzed ESI-MS² data on an identical compound under different collision-induced dissociation conditions. Data merging has significantly improved the precision of the identification of a chemical compound by 21-23% at a similarity score of 0.6. Thus, MassBank is useful for the identification of chemical compounds and the publication of experimental data. Copyright © 2010 John Wiley & Sons, Ltd.